Analysis Of The Propulsion And Maneuvering Characteristics Of Autonomous Underwater Vehicles And Their Strategic Defense - Komalasari, Rita; Mustafa, Cecep (Universitas Pertahanan RI, 2023)
This paper presents an essay that critically analyzes the propulsion and maneuvering characteristics of survey-style AUVs and their development for military applications. The study aims to uncover the strategic significance and transformative potential of innovative contributions, including biomimetic propulsion, AI-driven maneuvering, swarm-scoped autonomy, integrated power solutions, and comprehensive data fusion. Drawing upon an extended version of the Technology Acceptance Model (TAM), the essay explores user attitudes, strategic alignment, system performance enhancements, and environmental interactions. The methodology combines a comprehensive literature review, case study analysis, and examination of policy documents. The study's outcomes offer novel insights into bridging the gap between biology and engineering through biomimetic propulsion, enhancing AUV maneuverability with AI-driven strategies, revolutionizing military operations with swarm autonomy, extending AUV endurance via integrated power solutions, and achieving comprehensive data fusion for informed decision-making. The analysis showcases the evolving landscape of AUV technology and its strategic relevance, elucidating how these cutting-edge advancements reshape underwater exploration across civilian and military domains. Ultimately, this essay contributes to a comprehensive understanding of AUV capabilities and their potential for transformative impact in the underwater realm.